The Effect of Butterfly Pea Flower (Clitoria ternatea) Extract Addition on Total Dissolved Solids, Yeast Count, Total Acidity, and Organoleptic Properties of Water Kefir - Heni Rizqiati; Nurwantoro Nurwantoro; Sabina Fairuz Jinan Abdullah (Journal of Applied Food Technology, 2025)
This study aims to determine the effect of varying concentrations of butterfly pea flower extract (Clitoria ternatea) on kefir water in terms of total dissolved solids (TDS), total acidity, yeast count, and organoleptic properties. The materials used were dried butterfly pea flowers dissolved in mineral water (extract) and ingredients for producing kefir water. The experiment was conducted using a Completely Randomized Design (CRD) with extract concentrations of 0%, 0.5%, 1.0%, and 1.5% (v/v), each repeated five times. Data were analyzed using Analysis of Variance (ANOVA) and followed by Duncan's Multiple Range Test (DMRT) for the parameters of total dissolved solids, acidity, and yeast count. Organoleptic tests were analyzed using the non-parametric Kruskal-Wallis test, and if significant differences were found, they were followed by the Mann-Whitney test. The results of the study showed that the addition of butterfly pea flower extract at different concentration variations significantly affected (p<0.05) total dissolved solids, total acidity, and total yeast, with average values of total dissolved solids ranging from 10.90 to 10.40°Brix, total acidity from 0.05 to 0.21%, and total yeast of 1.60×10⁶ CFU/ml to 1.30×10⁶ CFU/ml. However, it did not affect taste, aroma, and texture, although color showed significant differences (p<0.05). Organoleptic test results yielded taste scores of 2.72 - 2.84, color scores of 1.44 - 4.88, aroma scores of 2.36 - 2.92, and texture scores of 2.04 - 2.36. However, the addition of butterfly pea flower extract at varying concentrations tended to reduce total soluble solids while increasing yeast count, total acidity, and enhancing color attributes in sensory evaluation.